2012
DOI: 10.1016/j.ajpath.2011.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Autoimmune Demyelination by Laquinimod via Induction of Brain-Derived Neurotrophic Factor

Abstract: Laquinimod is a promising, orally available compound that has been successfully evaluated in placebo-controlled phase II/III studies of relapsing-remitting multiple sclerosis (MS). Studies are ongoing to further define laquinimod's modulatory mechanisms. Analyses in the animal model of experimental autoimmune encephalomyelitis (EAE) demonstrate that laquinimod reduces infiltration of leukocytes into the central nervous system, induces a Th1 to Th2/3 shift, and suppresses Th17 responses. To evaluate the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
115
1
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 30 publications
6
115
1
3
Order By: Relevance
“…The influence of laquinimod on the immune system was studied in experimental autoimmune encephalomyelitis (EAE) (4)(5)(6)(7)(8)(9)(10)(11)(12), an autoimmune disease mediated by proinflammatory myelinreactive lymphocytes that cause CNS inflammation leading to demyelination and axonal loss. Laquinimod has also been effective in the treatment of other models of autoimmune diseases, specifically experimental autoimmune neuritis (13,14), lupus nephritis (15), and colitis (16).…”
mentioning
confidence: 99%
“…The influence of laquinimod on the immune system was studied in experimental autoimmune encephalomyelitis (EAE) (4)(5)(6)(7)(8)(9)(10)(11)(12), an autoimmune disease mediated by proinflammatory myelinreactive lymphocytes that cause CNS inflammation leading to demyelination and axonal loss. Laquinimod has also been effective in the treatment of other models of autoimmune diseases, specifically experimental autoimmune neuritis (13,14), lupus nephritis (15), and colitis (16).…”
mentioning
confidence: 99%
“…Sub-optimal responders to Copaxonemay greatly benefit from safe synergistic combination therapies such as Laquinimod. Currently in clinical trials for MS, Laquinimod has been reported to result in similar effects of GA including altering dendritic cells, inducing type II monocytes, increasing T and B regulatory cells, decreasing antigen presentation, and direct neuroprotective effects [104][105][106][107][108][109][110][111][112][113][114][115][116][117]. The novelty of this study is that a direct functional effect of GA on B lymphocytes has not been previously reported.…”
Section: Discussionmentioning
confidence: 82%
“…Axonal protection by LAQ was also observed in a rat model of optic neuritis [Sühs, 2007]. Also in patients with MS, LAQ treatment results in a significant and persistent increase in BDNF serum levels when compared with baseline and placebo-treated patients [Thöne et al 2012]. Furthermore, it was demonstrated that the attenuation of EAE by LAQ to be mediated by the reduction of overactive NMDA receptors of presynaptic terminal, while increasing GABAergic synaptic currents.…”
Section: Introductionmentioning
confidence: 94%
“…Recently it has been suggested that the beneficial effect of LAQ may be mediated by modulation of dendritic cells (DCs) affecting the antigen presentation capacity [Gurevich et al 2010;Thöne et al 2012;Jolivel et al 2013]. Under treatment with LAQ, both in murine models and in patients with MS, a reduction in the number of DCs has been observed, in addition to a reduced ability of these cells to induce the proliferation of CD4 + T cells as well as to stimulate the secretion of proinflammatory cytokines [Jolivel et al 2013].…”
Section: Introductionmentioning
confidence: 99%